Social Demographic Determinants of National Health Insurance Uptake among the Informal Sector Workers, Vihiga County, Kenya - Muranda Marion Agiza; Owenga Jane Adhiambo; Otieno David Odongo; Onguru Daniel Ogungu; Orende Merceline Awino (Research Aspects in Arts and Social Studies Vol. 7, 2023)
The study sought to ascertain the impact of demographic factors on the uptake of National Health Insurance among informal sector workers in Vihiga Sub-County. The informal sector employees in Vihiga Sub County were the study’s target demographic, and they were selected from the Sub County’s four wards. A representative sample of 384 was obtained through the use of cluster sampling and simple random sampling techniques. Data was gathered through the use of semi-structured questionnaires, and descriptive statistics were used for analysis. The findings showed that the adoption of national health insurance was highly correlated with elderly people above the age of 50, women, high levels of education, high income, households headed by women, and formal employment. Additionally, the adoption of national health insurance was significantly influenced by age, gender, the gender of the household head, level of education, employment status, and household monthly income. Enrollment in a health insurance scheme should be encouraged among the youth and male population to ensure that they have access to recommended care, receive quality care, and have better health outcomes.